Diversity-Oriented Synthesis of Highly Functionalized Alicycles across Dipolar Cycloaddition/Metathesis Reaction - Benke, Zsanett; Nonn, Melinda; Remete, Attila M.; Fustero, Santos; Kiss, Loránd (Synlett, 2021)
This Account gives an insight into the selective functionalization of some readily available commercial cyclodienes across simple chemical transformations into functionalized small-molecular scaffolds. The syntheses involved selective cycloadditions, followed by ring-opening metathesis (ROM) of the resulting azetidin-2-one derivatives or isoxazoline frameworks and selective cross metathesis (CM) by discrimination of the C=C bonds on the alkenylated heterocycles. The CM protocols have been described when investigated under various conditions with the purpose on exploring chemodifferentiation of the olefin bonds and a study on the access of the corresponding functionalized β-lactam or isoxazoline derivatives is presented. Due to the expanding importance of organofluorine chemistry in drug research as well as of the high biological potential of β-lactam derivatives several illustrative examples to the access of some fluorine-containing molecular entities is also presented in this synopsis.1 Introduction2 Ring C=C Bond Functionalization of Some Cycloalkene β-Amino Acid Derivatives across Chlorosulfonyl Isocyanate Cycloaddition3 Ring C=C Bond Functionalization of Some Cycloalkene β-Amino Acid Derivatives across Nitrile Oxide Cycloaddition4 Ring C=C Bond Functionalization of Some Cycloalkene β-Amino Acid Derivatives across Metathesis5 Functionalization of sSome Cyclodienes across Nitrile Oxide Cycloaddition6 Selective Synthesis of Functionalized Alicycles across Ring-Opening Metathesis7 Selective Synthesis of Functionalized Alicycles through Cross Metathesis8 Summary and Outlook9 List of Abbreviations
Keywords: metathesis; selectivity; β-lactam; isoxazoline; fluorine